2022
DOI: 10.1371/journal.pone.0264040
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural networks and genetic algorithm to predict and optimize greenhouse banana fruit yield through nitrogen, potassium and magnesium

Abstract: The excess of the chemical fertilizers not only causes the environmental pollution but also has many deteriorating effects including global warming and alteration of soil microbial diversity. In conventional researches, chemical fertilizers and their concentrations are selected based on the knowledge of experts involved in the projects, which this kind of models are usually subjective. Therefore, the present study aimed to introduce the optimal concentrations of three macro elements including nitrogen (0, 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…But several studies in other fields of biology have evidently confirmed that GRNN had better performance than MLP and RBF [ 29 , 63 , 97 ]. Also, according to a comparative analysis of the MLP and GRNN to optimize greenhouse banana fruit yield by Ramezanpour and Farajpour [ 98 ], their results have strongly stated that the GRNN was a more accurate technique than MLP in the prediction of evaluated parameters. In another study, the good performance of the GRNN technique for modeling and predicting in vitro seed germination in cannabis has been highlighted by Pepe et al ., [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…But several studies in other fields of biology have evidently confirmed that GRNN had better performance than MLP and RBF [ 29 , 63 , 97 ]. Also, according to a comparative analysis of the MLP and GRNN to optimize greenhouse banana fruit yield by Ramezanpour and Farajpour [ 98 ], their results have strongly stated that the GRNN was a more accurate technique than MLP in the prediction of evaluated parameters. In another study, the good performance of the GRNN technique for modeling and predicting in vitro seed germination in cannabis has been highlighted by Pepe et al ., [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the GRNN model is known for its ability to capture complex patterns and relationships in the data due to its non-linear nature [65]. It uses a radial basis function activation function, which allows it to approximate any continuous function with high accuracy [66]. This flexibility enables the GRNN model to effectively capture the intricate relationships between the concentrations of phytohormones and callogenesis [21] in petunia tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is particularly beneficial in the context of callogenesis prediction in petunia tissue culture, where historical data and patterns play a crucial role [20]. In contrast, the RBF model and MLP model lack this explicit memory capability, which may limit their ability to effectively capture long-term dependencies and generalize well to new data [66].…”
Section: Discussionmentioning
confidence: 99%
“…Computational intelligence approaches have also been applied in [19][20][21][22][23] with a focus on cost reduction, peak energy demand, energy saving, and DSM. Aiming at solving optimization problems, several studies have proposed genetic algorithms, including [24][25][26][27][28][29][30]. The results justify the applicability of the genetic algorithms for power utilization reduction, minimizing the electricity cost and peak-to-average ratio considering shifting and nonshifting loads via appliance scheduling.…”
Section: Literature Reviewmentioning
confidence: 99%